FAMILY SUPPORT SERVICES FOR VULNERABLE FAMILIES IN BULGARIA: BARRIERS AND CHALLENGES - Kotzeva, Tatyana; Mineva, Krasimira (Economy and Sociology, 2023)
Family support services are of crucial importance for families from vulnerable groups in order to ensure their normal access to the educational, health and social systems and to protect the child’s best interest in parenting. The aim of this paper is to review the key challenges in effectively delivering family services to vulnerable families in Bulgaria through a discussion of the main barriers and facilitators in family support provision. The analysis is based on the data from a small-scale survey including online survey with 40 organizations providers of family services; interviews with 15 professionals working in these organizations and a group discussion with the services providers from the Community Center for Early Childhood Development and Parental Support "Nadezhda" in the city of Burgas, Bulgaria. The main difficulties that the professionals came across in their work concerned convincing families to use the services, overcoming parents’ unwillingness to cooperate with professionals and denying or neglecting the child’s problem and handling the discrepancy between user’s expectations and delivered services. The survey data also outlined the proactive solutions and the directions for improvement in the quality of services: development of interaction and partnership with families from vulnerable groups; networking with other institutions and organizations to provide non-fragmented services; increasing the number of educational and health mediators that will increase parents’ motivation and encourage services take-up; providing integrated services in the community through mobile groups and fieldwork; overcoming prejudices and discriminative attitudes toward marginalized groups and raising the level of awareness of families toward delivered services and their effects on child’s wellbeing.